A Virtual Reality—Metaverse and Its Trends - Kamya Sharma (International Journal of Information Security Engineering, 2023)
In 1992, the concept of a metaverse was first introduced to the public. Metaverse, as its name implies, is a mashup of the terms "meta" and "universe," where "meta" is Greek for "beyond”. As a result, it means beyond our current understanding of the universe. It exists in the virtual world but feels just as real. In a metaverse, various virtual spaces are combined into a single, persistent, 3D environment. Metaverse enables users to experience immersive gaming, conduct business, socialize, buy and sell virtual properties, and enjoy immersive entertainment in a virtual world by interacting with their digital avatars. People can experience virtual and augmented versions of reality in metaverse. Basically, it means there is more to the universe than we realize. In recent news, Facebook announced it would rebrand its company family as metaverse-centered. Zuckerberg's press release brought it to the forefront of the public's attention. Literature has discussed metaverse technology since the 1990s, but this study presents an analysis of its bibliometric evolution. There has been tremendous attention paid to the metaverse in recent years due to a number of related technologies. There would be a realistic metaverse, where direct and physical interactions would be encouraged, with racial, gender, and physical disability concepts weakened, which would be highly beneficial to society.
Keywords: Virtual reality (VR); augmented reality (AR); digital avatars; metaverse; mixed reality (MR); online platforms; web realtime communication (WebRTC)